Seismic Assessment of Steel Frames Subjected to Multi-hazards - Badla, O. (Engineering, Technology & Applied Science Research, 2022)
This paper investigates the effects induced by thunderstorm downbursts to steel building structures that have been previously damaged during strong directivity ground motion events. To achieve this objective, one four-story steel moment-resisting frame that was tested at the E-defense laboratory, Japan was analyzed in the nonlinear range using OpenSees. The seismic response was numerically simulated, obtaining a satisfactory agreement with the experimental evidence, revealing that the effects of such wind events and vertical ground motions were significant. These effects should be addressed during the design of low and medium buildings subjected to initial damage and subsequent thunderstorm downbursts and the ductility demands on structures subjected to multi-hazards can be quantified. The wind loads are applied as an externally applied dynamic load and the revised ductility demands are determined directly. The obtained results are compared to what is expected by experimental tests.